Persepsi Masyarakat Aceh Timur Terhadap Pemekaran Wilayah Kabupaten Baru Bandar Khalifah di Aceh Timur - Abdul Aziz; Muliana (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2022)
This study aims to determine: Public perception of the discourse on the expansion of the new district of Bandar Khalifah in East Aceh. This research is a type of descriptive research. The population in this study is the people of East Aceh, while the sample in this study is an object/subject that has certain attributes determined by the researcher and then conclusions are drawn. Method. Data analysis used is validity test, reliability test, t-One sample test. The results of the study show that: the results of the calculations in the one sample test table can be seen that the t value (count) is 52,719. The value of df (degrees of freedom) or degrees of freedom is 0.000. Thus the alternative hypothesis (Ha) which states that the community has a good perception of the expansion of the new district of Bandar Khalifah in East Aceh is